Answer: n = 5m/(1 + m)
Step-by-step explanation:
The given equation is
m = n/(5 - n)
To solve for n, the first step is to cross multiply. We have
m(5 - n) = n
We would expand the parentheses on the left by multiplying each term inside with the term outside. It becomes
5m - mn = n
Adding mn to both sides, it becomes
5m - mn + mn = n + mn
5m = n + mn
on the right, n is a common factor of n and mn. By factorizing n, we have
5m = n(1 + m)
Dividing both sides of the equation by (1 + m), it becomes
5m/(1 + m) = n(1 + m)/(1 + m)
5m/(1 + m) = n
n = 5m/(1 + m)